2021
DOI: 10.25259/jmsr_109_2021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tourniquet use on total blood loss following total knee arthroplasty

Abstract: Objectives: Blood loss during total knee arthroplasty (TKA) can be a concern. Therefore, a tourniquet (TQ) is commonly used during the procedure to minimize this risk. However, the use of a TQ in TKA continues to be a matter of debate among orthopedic surgeons and is related to its advantages and disadvantages. We retrospectively evaluated the impact of applying the TQ on total blood loss following TKA in 276 patients. Methods: Patients were categorized into two groups: TQ and non- TQ. Demographics, surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
2
0
0
Order By: Relevance
“…Although the mean Hb drop for males (2.81 g/dL) was slightly higher than in females (2.66 g/dL), which correlated with other studies done in China [19] and Saudi Arabia [20], and the results from our study were not signifcant (p � 0.48). Tere is a wider range of surgeries that male participants underwent compared to their female counterparts in the study, as most females underwent hip and spine surgeries while men had more upper limb and ankle plates and screws.…”
Section: Advances In Orthopedicssupporting
confidence: 89%
See 1 more Smart Citation
“…Although the mean Hb drop for males (2.81 g/dL) was slightly higher than in females (2.66 g/dL), which correlated with other studies done in China [19] and Saudi Arabia [20], and the results from our study were not signifcant (p � 0.48). Tere is a wider range of surgeries that male participants underwent compared to their female counterparts in the study, as most females underwent hip and spine surgeries while men had more upper limb and ankle plates and screws.…”
Section: Advances In Orthopedicssupporting
confidence: 89%
“…Our study found no signifcant diference in the mean Hb drop in patients who used tourniquets during surgery (p � 0.39) even though the means showed a notable difference. Tis correlated to a study done in Saudi Arabia that found no diference in the use of tourniquets in TKR surgeries [20]. Te use of tourniquets has largely been associated with lower levels of bleeding in patients intraoperatively [24], contrary to the results of our study.…”
Section: Advances In Orthopedicssupporting
confidence: 84%